Optimalisasi Sistem Pengendalian Inters Pemerintah (SPIP) Melalui Pendekatan Manajemen Risiko - Rahmawati, Nadia; Irsyad, Irsyad; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2025)
To achieve good governance, governments are required to implement an internal control system that is effective, efficient, transparent, and accountable. One of the key instruments to support this objective is the Government Internal Control System (SPIP). However, SPIP implementation in many government institutions still faces various challenges, including weak leadership commitment, unsupportive organizational culture, and limited human resource capacity. To address these challenges, a more adaptive and systematic approach through risk management is essential. This study uses a library research method by reviewing relevant literature and previous studies related to SPIP implementation and risk management in the public sector. The results indicate that the application of risk management enhances the effectiveness of all SPIP components, namely the control environment, risk assessment, control activities, information and communication, and internal monitoring. The integration of risk management within SPIP not only supports the identification and mitigation of potential risks but also promotes a risk-aware culture within government organizations. Furthermore, optimization strategies such as strengthening leadership commitment, improving human resource capacity, integrating information technology, and conducting continuous monitoring are crucial in supporting risk-based SPIP implementation. Overall, the implementation of SPIP based on risk management contributes to improved accountability, transparency, organizational performance in government institutions.